ILCA to expand forage seed work - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
The International Livestock Centre for Africa (ILCA) is to establish a forage seed unit at its Debre Zeit research station, south of Addis Ababa. It also intends to expand the activities of the Pasture Network for Eastern and Southern Africa...